2019
DOI: 10.1111/gcbb.12642
|View full text |Cite
|
Sign up to set email alerts
|

DMPP reduced nitrification, but not annual N2O emissions from mineral fertilizer applied to oilseed rape on a sandy loam soil

Abstract: Direct field emissions of nitrous oxide (N2O) may determine whether biodiesel from oilseed rape (Brassica napus L.) fulfills the EU requirement of at least 50% reduction of greenhouse gas emissions as compared to fossil diesel. However, only few studies have documented fertilizer N emission factors (EF) and mitigation options for N2O emissions from oilseed rape cropping systems. We conducted a field experiment with three N levels (0, 171, and 217 kg/ha), where the N fertilizer was applied as ammonium sulfate n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…On sandy to silt loam soils, Vinzent et al (2018) reported EFs ranging from 0.19-0.50% for WOSR over three seasons in Germany. Thers et al (2019) also reported much lower EFs (0.28-0.36%) from mineral N applied to WOSR on a sandy loam soil in Denmark. Ruser et al (2017) suggested an EF of 0.6% for WOSR at a fertilizer rate of 200 kg N ha −1 .…”
Section: Re-assessment Of the Tier 1 Efs For Irish Agricultural Systemsmentioning
confidence: 89%
“…On sandy to silt loam soils, Vinzent et al (2018) reported EFs ranging from 0.19-0.50% for WOSR over three seasons in Germany. Thers et al (2019) also reported much lower EFs (0.28-0.36%) from mineral N applied to WOSR on a sandy loam soil in Denmark. Ruser et al (2017) suggested an EF of 0.6% for WOSR at a fertilizer rate of 200 kg N ha −1 .…”
Section: Re-assessment Of the Tier 1 Efs For Irish Agricultural Systemsmentioning
confidence: 89%
“…Brassica napus L. (AACC, 2n=38), known as rapeseed, an amphidiploid species formed by natural hybridization of two diploid progenitors, Brassica rapa (AA, 2n=20) and Brassica oleracea (CC, 2n=18), is the second most important oilseed crop and provides approximately 13%–16% of vegetable oil globally for edible and biofuel (Jian et al, 2016; Lohani et al, 2020; Song et al, 2020). Furthermore, rapeseed is the main crop converted to biofuel in the form of rapeseed methyl ester in the EU (Forleo et al, 2018; Thers et al, 2019). Improving rapeseed yield and oil content is necessary for sustainable biofuel production, which has become one of the main environmental challenges of the 21st century.…”
Section: Introductionmentioning
confidence: 99%